Arrythmias: An Updated Overview for Healthcare Professionals - Jabour , Hashima Makki Mohammed; Alshammri , Alanood Gadeer; Almakadi , Galla Nader Mobark; Aleid , Afnan Mohammed; Alfaran, Malika Haider; Alfazi, Raed Muawwadh Aifan; Maslof, Mohammed Ahmed Hassan; Alanazi , Ashwaq Awad; Almutairi, Talal Nasser (Journal of Ecohumanism, 2024)
Background: Arrhythmias are abnormalities in the heart’s rhythm, deviating from the normal sinus rhythm, the heart’s physiologically appropriate rhythm. The heart’s electrical impulses initiate from the sinoatrial node and propagate through the atrioventricular node, bundle of His, and Purkinje fibers. Disruption in this sequence leads to arrhythmias, categorized into bradyarrhythmias (slow heart rate) and tachyarrhythmias (fast heart rate). Arrhythmias vary in their pathophysiology and clinical consequences, making early diagnosis and appropriate management essential for patient outcomes. Aim: This article provides an updated overview of arrhythmias, including their types, causes, diagnostic methods, and management strategies, to guide healthcare professionals in their clinical practice. Methods: The article reviews current literature, examining the classification, diagnosis, and treatment of arrhythmias. It emphasizes the clinical significance of arrhythmias, the use of electrocardiograms (EKG), and the importance of monitoring and diagnostic tools like ambulatory EKG and loop recorders for paroxysmal arrhythmias. Results: Arrhythmias present in a range of forms, from supraventricular tachycardias like atrial fibrillation (AF) and atrial flutter to life-threatening ventricular tachycardias and fibrillation. Diagnostic strategies vary from initial EKGs to more advanced ambulatory techniques. Treatment approaches include rate control, rhythm control, pharmacologic therapy, and interventions such as cardioversion and catheter ablation. Conclusion: Arrhythmias are a diverse group of heart conditions that can significantly impact health. Early recognition, accurate diagnosis, and appropriate management are critical for improving patient outcomes. Healthcare professionals must remain updated on evolving treatment modalities, particularly as arrhythmia pathophysiology and management strategies continue to advance.